Promising reagents for the extraction of strategic metals from difficult-to-enrich mineral raw materials - Tamara N. Matveeva; Nadezhda K. Gromova; Lyudmila B. Lantsova (Записки Горного института)
The need of the mining and processing industry for new types of directional reagents is due to the deterioration of the material composition of the processed ores. Low Au content (less than 0.5-1.0 g/t), finely dispersed Au inclusions (0.1-10.0 microns) in the ore, similar properties of the separated minerals have an extremely negative effect on flotation performance when using traditional reagents, which leads to significant losses of valuable metal with enrichment tailings. Expanding the range of domestic flotation reagents based on the latest achievements of fundamental research and their targeted application at mining and processing companies will compensate for the negative impact of the mineral composition of raw materials and ensure maximum extraction of strategic metals from difficult-to-enrich ores. The use of modern research methods (scanning electron and laser microscopy, UV spectrophotometry, XRF and chemical analysis) made it possible to visualize the adsorption layer of new reagents-collectors of a number of dithiocarbamates with different structures of a hydrocarbon radical and an organic modifier on the surface of gold-containing sulfides. The amount of adsorbed reagents on the surface of minerals has been experimentally determined. The specific features of the fixation of reagents on minerals of various compositions led to optimal correlations of their consumption in the flotation process. Scientifically based reagent regimes ensured an increase in the gold content in the concentrate and a decrease in the loss of gold with tailings by 5-6 % during flotation enrichment of the refractory ore of the Malinovskoe deposit.